ACCELERATING KERR-NEWMAN-NUT/ CONFORMAL FIELD THEORY CORRESPONDENCE - Irawan, Andika
The holographic principle relates quantum theory of gravity to quantum field theory in fewer dimensions. In the last decade, one study about the application of holographic principle to black holes is the Kerr/conformal field theory (CFT) correspondence, which conjectured that Kerr extreme black hole is holographically dual to a two-dimensional CFT. In this thesis, the correspondence was considered to the accelerating Kerr-Newman-NUT black hole/CFT. The study was focused on extreme black hole which satisfy SL(2,R) × U(1) isometry group. It posessed a curved space-time in the asymptotic which satisfy the asymptotic symmetry group (ASG). The commutation of the generators were satisfying Virasoro algebra that contains a central charge. On the other hand, Virasoro algebra exists in the formulation of conformal field theory, it leads to the correspondence between black holes and conformal field theory. Thus, the thermodynamic aspects of black hole such as temperature and entropy can be studied microscopically in succession using the Frolov-Thorne vacuum state and the Cardy formula, rather than macroscopically using the Bekenstein-Hawking formulation. The calculations in this study were carried out analytically so that the result of Bekenstein-Hawking entropy agreed to the Cardy entropy.